EFFECTIVE ELEMENTS OF TECHNOLOGY OF CULTIVATION OF SOYBEANS IN THE NORTHERN STEPPES CONDITIONS - Крамарьов, С. М.; Артеменко, С. Ф.; Писаренко, П. В. (Scientific Progress & Innovations, 2014)
Inoculation and incrustation of seeds in technology every culture is important. Treatment of inoculum promising strains of nitrogen-fixing bacteria positive influence on the potential productivity of nitrogen fixation and consequently the harvest of this crop. On the plots, where the seeds of inoculation were treated strains 46 and a, the number of nodules on the same plant grew 3.3 times, and their weight in 2 times. These crops are formed maximum area leaves 39,0-40,0 thousand m2/ha)that was beyond the control plots 17.8-20,8%. The number of beans increased by 11.7-17,4%. Pre-sowing seed inoculation azotfiksatsii strains of root nodule bacteria X9; a; 46 have provided the best conditions for nitrogen fixation and high seed productivity of soy. The yield of soybean seeds, which produced the pre-sowing treatment of seeds per-looking strains of nitrogen-fixing bacteria, increased by 11.9 15.2%. Incrustation of seeds with foaming agent Mars EL and drug Antistress, which contains potassium phosphate, together with molybdenum and boron put additional field germination rate is 10.8-11.8 percent. The use of these drugs was provided by the formation of a greater height of soybean 9.6-14.2%and the number of nitrogen-fixing nodules increased by 26.3-39,5%. Soybean crops have formed a large area of assimilating leaf surface by 26.7% with the use of the drug antistress at the incrustation of seeds, and together with complexions metals molybdenum and boron this figure increased to 53.5%. The best yield of 2.18 t/ha, formed soybean crops using for incrustation of inoculum preparation Antistress (200 g/t) of complexions and metals molybdenum and boron (100 g/t each) and the crickets granilit (2.5 l/t).